2015
DOI: 10.2319/041615-255.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic bracket bonding without previous adhesive priming: A meta-regression analysis

Abstract: Objective: To determine the consensus among studies that adhesive resin application improves the bond strength of orthodontic brackets and the association of methodological variables on the influence of bond strength outcome. Materials and Methods: In vitro studies were selected to answer whether adhesive resin application increases the immediate shear bond strength of metal orthodontic brackets bonded with a photo-cured orthodontic adhesive. Studies included were those comparing a group having adhesive resin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…These results are in line with previous study, which also found significant differences between the groups with and without adhesives 13 . However, a recent study showed that brackets fixed without adhesive presented a debonding rate after 12 months similar to that of brackets fixed with adhesive 15,16 . Other study showed that the penetration of the liquids into narrow capillaries, such as microporosities of etched enamel was influenced by properties of the liquid, such as viscosity and the surface free energy of the capillary wall 17 .…”
Section: Discussionmentioning
confidence: 94%
“…These results are in line with previous study, which also found significant differences between the groups with and without adhesives 13 . However, a recent study showed that brackets fixed without adhesive presented a debonding rate after 12 months similar to that of brackets fixed with adhesive 15,16 . Other study showed that the penetration of the liquids into narrow capillaries, such as microporosities of etched enamel was influenced by properties of the liquid, such as viscosity and the surface free energy of the capillary wall 17 .…”
Section: Discussionmentioning
confidence: 94%
“…The literature has shown that size and design of the bracket base affect the bond strength to the enamel. 4,5,14,20,23,[6][7][8][9][10][11][12][13] Altmann et al 4 showed that bracket base area is an important variable in SBS. Also, it is known that the bracket base curvature should adapt to the tooth surface, allowing small thickness of resin between the base and the enamel, otherwise it could result in a weak interface due to the inherent mechanical properties of the resin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is known that the bracket base curvature should adapt to the tooth surface, allowing small thickness of resin between the base and the enamel, otherwise it could result in a weak interface due to the inherent mechanical properties of the resin. 4 Finite element analysis provided a clearer insight of the stress distribution and showed that the greater bracket base adaptation on the tooth surface, the distribution of forces along its surface will be more uniform. 24 In addition, laser parameters such as power, wavelength, frequency, scanning speed and original article Moreira FC, Jacob HB, Vaz LG, Guastaldi AC the exposure of the bracket surface area, can promote different outcomes for SBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite adhesive systems can cause enamel loss up to 10  μ m [8]. Since metal brackets are opaque, light activation for 20 seconds may not be enough, while light activation for 40 seconds can increase the bond strength approximately by 9-10 MPa and create excessively firm bonding in some enamel areas [9]. The other problem with composite resin bonded orthodontic brackets and tubes is decalcification of the enamel and white spot lesions.…”
Section: Introductionmentioning
confidence: 99%